Not so different : what you really want to ask about having a disability - Burcaw, Shane (Roaring Brook Press, 2017)
A picture book answering the questions young children ask Shane Burcaw about his wheelchair and life with Spinal Muscular Atrophy with equal parts optimism, humor, and empathy.